Pengaruh Teknologi Finansial dan Inklusi Keuangan Terhadap Ketimpangan Pendapatan di Negara ASEAN-6: (The Impact of FinancialTechnology and Financial Inclusion on the Income Inequality in ASEAN-6 Countries) - Pratama, Yonanda Yudha; Titik, Crisanty Sutristyaningtyas (e-Journal Ekonomi Bisnis dan Akuntansi, 2024)
This study aims to analyze the long-term and short-term effects of financial technology and financial inclusion on income inequality in ASEAN-6 countries, namely Indonesia, Malaysia, Singapore, Thailand, Philippines and Vietnam, for the period between 2011 and 2022. Indicators used in This research is income inequality using the Gini coefficient, financial inclusion using financial inclusion indicators based on the Sarma model and data on e-money usage as an indicator of financial technology. The data analysis technique used is Panel Auto Regressive Distributed Lag (ARDL). The results of this study found that in the long term the financial technology variable has a significant negative effect, while in the short term it has no significant effect on income inequality in ASEAN-6, and the financial inclusion variable in the long term has a significant positive effect, whereas in the short term it has no significant effect on income inequality in ASEAN-6.